Analisis Pusat Pertumbuhan Wilayah di Kabupaten Pasaman Barat Berdasarkan Perhitungan Hirarki dengan Analisis Scalogram - Meilani Dwi Astuti; Dasrizal Dasrizal; Rika Despica (Journal on Education, 2024)
This research is motivated by the unequal economic growth in West Pasaman Regency in its respective regions. This analysis can be seen from, 1) economic growth, 2) physical growth, 3) spatial patterns of regional growth. This research is a quantitative descriptive research type, the population in this research is the number of service facilities. The sample for this research is all sub-districts in West Pasaman Regency with the sampling technique in this research being total sampling. To see economic growth there are 2 indicators, namely GRDP and Per Capita Income, to see physical growth there are 4 indicators, namely data analysis used, namely, scalogram analysis, determining the function weight of service facilities, determining regional centrality and hierarchy index, serviceability ratio of service facilities. To see the spatial pattern of regional growth, there are 2 indicators, namely point coordinates and nearest neighbor analysis.The results of this research are 1) Economic growth in West Pasaman Regency experienced fluctuations in 2014-2023 with per capita income of Rp. 43 428.06 billion rupiah, 2) Physical Growth of the West Pasaman Regency Region is located in Pasaman District with Hierarchy Category I where this area has complete facilities, namely educational facilities, health facilities, economic facilities and public facilities, 3) Spatial pattern of growth of the Regency Area West Pasaman is Dispersed or scattered.